Studi Pembuatan Minuman Serat Alami Yang Kaya Î²-Karoten - Rusmarilin, Herla; Sair Siregar, Muhammad; Syukri Tbn, Irfan (Agrintech: Jurnal Teknologi Pangan dan Hasil Pertanian, 2017)
Research on the Study of Natural Fibers Beverage Making Rich Beta Carotene method completely randomized design (CRD) with two (2) replicates. The first factor is the ratio of stem kale and skin melinjo, namely: S1 = 100: 0%, S2 = 75: 25%, S3 = 50: 50%, S4 = 25: 75%, S5 = 0: 100 The second factor is the addition of Carrots juice (W), which consists of three levels, namely: W1 = 30% = 40% W2, and W3 = 50%. The parameters observed: Moisture, Ash levels, Fiber Content, Content Beta carotene, water absorption, oil absorption, organoleptic color, flavor and aroma. The statistical analysis was obtained, that the ratio of water spinach stems and bark melinjo provide highly significant effect (P <0.01) on water content, ash content, Fiber Content, Content Beta Carotene, water absorption, oil absorption Organoleptik flavor and aroma as well as had no significant effect (P> 0.05) to organoleptic color. And the addition of carrot juice provides highly significant effect (P <0.01) on water content, ash content, content of fiber, beta-carotene content, water absorption, oil absorption, organoleptic aroma, color and flavor. Interaction provides highly significant effect (P> 0.01) on water content and water absorptionÂ Keywords: Stem kale, Caucasian Melinjo, Carrot.